Batik in Contemporary Fashion Design (Swimwear Case Study): Implications for Teaching and Learning in Fashion Education - Wesnina; Yoga Matin Albar; Heru Miftakhudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study investigates the incorporation of Batik into fashion design curricula, focusing on how it affects students' understanding of cultural heritage, sustainability, and ethical design practices. A qualitative technique was used to collect data, which included literature reviews, case studies, and semi-structured interviews with fashion educators and students. The findings reveal that educators incorporate Batik into curricula through theoretical modules on its cultural history, hands-on workshops teaching traditional Batik techniques, and projects exploring modern applications such as swimwear and sportswear design. Collaborations with local artisans further enhance students’ appreciation of Batik’s cultural and social significance, while assignments emphasizing ethical reflection help address concerns about cultural appropriation and responsible design. The findings show that 90% of students reported enhanced understanding of cultural history, with many expressing a greater appreciation for Batik's function in storytelling and identity preservation. Furthermore, Batik's eco-friendly production methods taught students about sustainability, which informed their ideas on slow fashion and natural colouring techniques. Despite its advantages, issues such as time limits, material adaptation difficulties, and limited availability to craftspeople were identified. The study emphasizes the significance of refining teaching methodologies to overcome obstacles and ensuring that cultural education stays fundamental to modern design innovation.